2012
DOI: 10.1038/ajh.2012.97
|View full text |Cite
|
Sign up to set email alerts
|

Regorafenib Induces Rapid and Reversible Changes in Plasma Nitric Oxide and Endothelin-1

Abstract: These findings indicate that regorafenib induces a coordinated and reversible suppression of NO and stimulation of ET-1. Whether NO and ET-1 might predict therapeutic efficacy in these patients requires further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…In an attempt to unravel the mechanism of hypertension, we measured neurohormones in patients with metastatic renal cancer or gastrointestinal stromal cancer who were treated with the receptor tyrosine kinase inhibitor (RTKI) sunitinib for the first time, and observed that the rise in BP was associated with a two to three-fold rise in circulating ET-1 levels [18]. This activation of the ET-1 system has been confirmed in another clinical study with the RTKI regorafenib, supporting the view that this activation is a common response to treatment that interferes with the VEGF-signaling pathway [19]. In subsequent studies in rats we could replicate the clinical findings [20].…”
Section: Elevated Endothelin Following Antiangiogenic Treatmentmentioning
confidence: 73%
“…In an attempt to unravel the mechanism of hypertension, we measured neurohormones in patients with metastatic renal cancer or gastrointestinal stromal cancer who were treated with the receptor tyrosine kinase inhibitor (RTKI) sunitinib for the first time, and observed that the rise in BP was associated with a two to three-fold rise in circulating ET-1 levels [18]. This activation of the ET-1 system has been confirmed in another clinical study with the RTKI regorafenib, supporting the view that this activation is a common response to treatment that interferes with the VEGF-signaling pathway [19]. In subsequent studies in rats we could replicate the clinical findings [20].…”
Section: Elevated Endothelin Following Antiangiogenic Treatmentmentioning
confidence: 73%
“…32,36,37 Also the urinary excretion of ET-1, reflecting increased renal ET-1 production, is enhanced after VSP inhibition. 66 One may pose the question, therefore, whether activation of the ET system contributes to the renal injury induced by VSP inhibition.…”
Section: Role Of Activation Of the Endothelin Systemmentioning
confidence: 99%
“…31 In patients with a gastrointestinal stromal tumor, regorafenib treatment was associated with a reversible suppression of NO. 32 In a study in healthy volunteers, intra-arterial infusion of bevacizumab in the forearm acutely reduced the vasodilator response to acetylcholine, consistent with decreased NO availability. 33 Conversely, systemic administration of sunitinib for 1 week in patients, only inducing a 5 mm Hg BP rise, was not associated with diminished forearm vasodilator response to acetylcholine, leading the authors to conclude that reduced endothelium-dependent vasodilatation does not precede the developmental phase of hypertension after sunitinib treatment.…”
Section: Mechanism Of Hypertension Decrease In No Bioavailabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…18 We have reported both a rapid rise in plasma ET-1 in patients receiving regorafenib, a TKI, with rapid normalization of ET-1 levels after therapy is stopped. 19 In several preclinical models, the rise in BP induced by antiangiogenic therapy is largely prevented by the co-administration of an endothelin receptor antagonist, providing strong evidence implicating the ET-1 pathway in antiangiogenic therapy induced hypertension. 16, 20 The source of ET-1 and the mechanisms linking VEGF inhibition to ET-1 activation remain to be elucidated.…”
Section: Pathophysiology Of Antiangiogenic Therapy-induced Hypertensionmentioning
confidence: 99%